Analysis of noise annoyance complaints in the city of Milan, Italy. (September 2020) - Zambon, G.; Muchetti, S.S.; Salvi, D.; Angelini, F.; Brambilla, G.; Benocci, R.
Abstract: The paper describes the analysis of noise annoyance complaints submitted by citizens to the Municipality of Milan, Italy, from years 2000 to 2015. These complaints have been organized in a database and analysed according to: i) types of noise sources (technical facilities, music, transport infrastructures, etc.), ii) activities (retail and catering businesses, production, service sector, etc.) and iii) outcomes of the complaints inspection by local authorities. In addition, by means of a Geographic Information System (GIS) software, the spatial distribution of complaints has been determined according to the noise source type and activities, including also a geo-statistical representation by complaints density maps. The results show that, despite the dominant noise source in urban areas is mainly the road traffic, the other noises, such as those from industrial facilities, constructions and social activities (parties, fairs and open air markets, residential noise, etc.), are perceived as more disturbing. Since 2007, the number of noise complaints (about 100-150 complaints/year) is almost constant across the years. However, these complaints are expected to increase due to the growing and spreading of leisure activities, malls, exhibition centres and event venues, observed for the years 2014-2015.